2013
DOI: 10.1177/1077801213486328
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Palestinian Physicians Toward Wife Abuse

Abstract: The article presents results from a larger survey, which examined the attitudes and perceptions of Palestinian physicians (N = 396) toward wife abuse. The instrument was a self-administered questionnaire, with open-ended questions in which participants expressed their definitions of wife abuse, their perceptions of the causes of wife abuse, and their perceptions of appropriate interventions with wife abuse. The relevance of the sociocultural contexts of Palestinian society in particular and Arab societies in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Accordingly, their sense of identity and cultural vitality are constantly challenged. Studies also portrayed the Palestinian masculinity in Israel as highly affected by sex-role stereotypes, negative and traditional attitudes toward women, non-egalitarian marital role expectations, and familial patriarchal beliefs (Haj-Yahia, 2013). In this context, Khoury (2018) examined the experiences of Palestinian fathers in egalitarian families and described their attempts to define their fatherhood between their conservative immediate surroundings and their life as part of a marginalized minority.…”
Section: Palestinian Fatherhood As Intersectionalmentioning
confidence: 99%
“…Accordingly, their sense of identity and cultural vitality are constantly challenged. Studies also portrayed the Palestinian masculinity in Israel as highly affected by sex-role stereotypes, negative and traditional attitudes toward women, non-egalitarian marital role expectations, and familial patriarchal beliefs (Haj-Yahia, 2013). In this context, Khoury (2018) examined the experiences of Palestinian fathers in egalitarian families and described their attempts to define their fatherhood between their conservative immediate surroundings and their life as part of a marginalized minority.…”
Section: Palestinian Fatherhood As Intersectionalmentioning
confidence: 99%
“…Furthermore, the same survey found that 30.2% of abused Palestinian wives (24% and 37.7% from the WB and GS, respectively) reported that they had left their homes and sought help, support, and protection from their fathers, brothers, or relatives. In contrast, the survey revealed that only 0.7% of the abused Palestinian wives, from both the WB and GS, reported seeking advice and counseling from a formal social organization or women’s center (Haj-Yahia, 2013a).…”
Section: Introductionmentioning
confidence: 95%
“…Despite these high rates of wife abuse and assault in Palestinian society in the WB and GS, research has shown that abused wives in this society rarely seek help from official organizations as a mode of coping with their husbands’ abusive and assaultive behaviors. For the most part, they prefer keeping their suffering to themselves or seeking advice and protection from their families of origin (Btoush & Haj-Yahia, 2008; Haj-Yahia, 2000b, 2002b, 2013a). The 2011 PCBS survey revealed that 65.3% of abused and assaulted wives (64.8% and 66% from the WB and GS, respectively) indicated that they did not tell anyone about their experience with abuse and assault.…”
Section: Introductionmentioning
confidence: 99%